Reciprocal regulation of enterococcal cephalosporin resistance by products of the autoregulated yvcJ-glmR-yvcL operon enhances fitness during cephalosporin exposure. - Dušanka Djorić; Samantha N Atkinson; Christopher J Kristich (PLoS Genetics, 2024)
Enterococci are commensal members of the gastrointestinal tract and also major nosocomial pathogens. They possess both intrinsic and acquired resistance to many antibiotics, including intrinsic resistance to cephalosporins that target bacterial cell wall synthesis. These antimicrobial resistance traits make enterococcal infections challenging to treat. Moreover, prior therapy with antibiotics, including broad-spectrum cephalosporins, promotes enterococcal proliferation in the gut, resulting in dissemination to other sites of the body and subsequent infection. As a result, a better understanding of mechanisms of cephalosporin resistance is needed to enable development of new therapies to treat or prevent enterococcal infections. We previously reported that flow of metabolites through the peptidoglycan biosynthesis pathway is one determinant of enterococcal cephalosporin resistance. One factor that has been implicated in regulating flow of metabolites into cell wall biosynthesis pathways of other Gram-positive bacteria is GlmR. In enterococci, GlmR is encoded as the middle gene of a predicted 3-gene operon along with YvcJ and YvcL, whose functions are poorly understood. Here we use genetics and biochemistry to investigate the function of the enterococcal yvcJ-glmR-yvcL gene cluster. Our results reveal that YvcL is a DNA-binding protein that regulates expression of the yvcJ-glmR-yvcL operon in response to cell wall stress. YvcJ and GlmR bind UDP-GlcNAc and reciprocally regulate cephalosporin resistance in E. faecalis, and binding of UDP-GlcNAc by YvcJ appears essential for its activity. Reciprocal regulation by YvcJ/GlmR is essential for fitness during exposure to cephalosporin stress. Additionally, our results indicate that enterococcal GlmR likely acts by a different mechanism than the previously studied GlmR of Bacillus subtilis, suggesting that the YvcJ/GlmR regulatory module has evolved unique targets in different species of bacteria.